CORRELATION AND PATH ANALYSIS STUDY OF SEED COAT COLOUR AND SEED DETERIORATION IN GREEN GRAM (VIGNA RADIATA L.) - ANIMESH PATHAK; S. K. CHAKRABARTI (The Bioscan, 2014)
The present study was undertaken to record the relationship between seed coat colour and seed deterioration. Other seed characters like germination percentage speed of germination, seedling fresh and dry weight, seed vigour, seed protein content, hundred seed weight and electrical conductivity of leachates were also studied for seeds with ‘Yellow’, ‘Green’ and ‘Brown’ seed coat colour. The correlation coefficient of pooled data of three years in different location indicated that germination percentage has got positive and significant correlation (0.798) with vigour index but negative significant correlation with hundred seed weight and electrical conductivity (-0.612). Path analysis of pooled data of three years has indicated that the germination percentage has got negative direct effects on electrical conductivity. The maximum direct effect has exhibited by root-shoot ratio followed by vigour index. As we have consider rate of seed deterioration in nine varieties of Vigna radiata with three different seed coat colours, from our present study it can be concluded that depending on electrical conductivity results, variety under green seed coat colour can be ranked as best as they showed less deterioration rate (0.09 to 0.15μS/cm) and highest deterioration (0.18 to 0.26 μS/cm) was found in case of seed with yellow seed coat colour. Varieties with green seed coat colour recorded maximum germination percentage, which can be selected for sowing purpose leading to maximum yield and the same varieties having less deterioration rate can be stored for a longer period.